In vitro comparison of linear vs triangular screw configuration to stabilize complete uniarticular parasagittal fractures of the proximal phalanx in horses - Labens, Raphael; Khairuddin, Nurul Hayah; Jermyn, Kieri; Syed Waseem Ahmad, Sharifah Roohi (Wiley-Blackwell Publishing, 2019)
Objective To assess fracture gap reduction and stability of linear vs triangular 4.5‐mm lag screw repair of experimental, uniarticular, and complete forelimb proximal phalanx (P1) fractures. Study design Experimental. Sample population Fourteen equine cadaver limbs/horses. Methods Simulated fractures were repaired with 2 lag screws under 4‐Nm insertion torque (linear repair). Computed tomography (CT) imaging was performed with the leg unloaded and loaded to forces generated while walking. The fracture repair was revised to include 3 lag screws placed with the same insertion torque (triangular repair) prior to CT. The width of the fracture gap was assessed qualitatively by 2 observers and graded on the basis of gap measurements relative to the average voxel size at dorsal, mid, and palmar P1 sites. Interobserver agreement was assessed with Cohen's κ. The effect of repair type, loading condition, and measurement site on fracture gap grades was evaluated by using Kendall's τ‐b correlation coefficients and paired nonparametric tests. Significance was set at P ≤ .05. Results Agreement between loading and fracture gap widening was fair in triangular (κ = 0.53) and excellent in linear (κ = 0.81) repairs. Loading resulted in fracture gap distraction in linear repairs (Plinear = .008). Triangular repairs reduced fractures better irrespective of loading (Punloaded = .003; Ploaded < .001). The type of repair was not correlated with fracture gap grades at unloaded mid and loaded dorsal P1 sites. Conclusion Repair of uniarticular complete parasagittal fractures with a triangular screw configuration improved in vitro fracture gap reduction and stability. Clinical significance Triangular lag screw repair likely improves biomechanical conditions during postoperative weight bearing.